Symptomatic Morgagni Hernia Misdiagnosed As Chilaiditi Syndrome - Vallee, Phyllis A (Western Journal of Emergency Medicine, 2011)
Chilaiditi syndrome, symptomatic interposition of bowel beneath the right hemidiaphragm, is uncommon and usually managed without surgery. Morgagni hernia is an uncommon diaphragmatic hernia that generally requires surgery. In this case a patient with a longstanding diagnosis of bowel interposition (Chilaiditi sign) presented with presumed Chilaiditi syndrome. Abdominal computed tomography was performed and revealed no bowel interposition; instead, a Morgagni hernia was found and surgically repaired. Review of the literature did not reveal similar misdiagnosis or recommendations for advanced imaging in patients with Chilaiditi sign or syndrome to confirm the diagnosis or rule out other potential diagnoses. [West J Emerg Med. 2011;12(1):121-123.]